On Acute Gene Expression Changes after Ventral Root Replantation - Risling, Marten; Ochsmann, Thomas; Carlstedt, Thomas; Lindå, Hans; Plantman, Stefan; Rostami, Elham; Angeria, Maria; Sköld, Mattias K. (Frontiers in Neurology, 2011)
Replantation of avulsed spinal ventral roots has been show to enable significant and useful regrowth of motor axons in both experimental animals and in human clinical cases, making up an interesting exception to the rule of unsuccessful neuronal regeneration in CNS. Compared to avulsion without repair, ventral root replantation seems to rescue lesioned motoneurons from death. In this study we have analyzed the acute response to ventral root avulsion and replantation in adult rats with gene arrays combined with cluster analysis of gene ontology search terms. The data show significant differences between rats subjected to ventral replantation compared to avulsion only. Even though number of genes related to cell death is similar in the two models after 24 hours, we observed a significantly larger number of genes related to neurite growth and development in the rats treated with ventral root replantation, possibly reflecting the neuroregenerative capacity in the replantation model. In addition, an acute inflammatory response was observed after avulsion, while effects on genes related to synaptic transmission were much more pronounced after replantation than after avulsion alone. These data indicate that the axonal regenerative response from replantation is initiated at an earlier stage than the possible differences in terms of neuron survival. We conclude that this type of analysis may facilitate the comparison of the acute response in two types of injury.